2013
DOI: 10.4254/wjh.v5.i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea and respiratory muscle strength in end-stage liver disease

Abstract: AIM:To investigate the prevalence of chronic dyspnea and its relationship to respiratory muscle function in end-stage liver disease. METHODS:Sixty-eight consecutive, ambulatory, Caucasian patients with end-stage liver disease, candidates for liver transplantation, were referred for preoperative respiratory function assessment. Forty of these (29 men) were included in this preliminary study after applying strict inclusion and exclusion criteria. Seventeen of 40 patients (42%) had ascites, but none of them was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 31 publications
0
38
1
Order By: Relevance
“…Even though several studies using standard techniques for evaluating acid-base equilibrium could not find any metabolic acid-base disorders, they reported the most well-established acid-base disorder in chronic liver disease, respiratory alkalosis, 30,31,[40][41][42] with a more pronounced hypocapnia in patients with severe liver disease or viral hepatitis. 37,43,44 While the reason for this commonly observed respiratory acidbase disorder is not ultimately clear, there are several theories and underlying conditions leading to dyspnoea and compensatory hyperventilation. 45,46 While massive ascites and/or hepatic hydrothorax 47 cause hypoxaemia and thus hyperventilation, hyperammonaemia and hepatic encephalopathy 48 induce hyperventilation per se.…”
Section: Alkalinising Factors In Patients With Liver Cirrhosismentioning
confidence: 99%
“…Even though several studies using standard techniques for evaluating acid-base equilibrium could not find any metabolic acid-base disorders, they reported the most well-established acid-base disorder in chronic liver disease, respiratory alkalosis, 30,31,[40][41][42] with a more pronounced hypocapnia in patients with severe liver disease or viral hepatitis. 37,43,44 While the reason for this commonly observed respiratory acidbase disorder is not ultimately clear, there are several theories and underlying conditions leading to dyspnoea and compensatory hyperventilation. 45,46 While massive ascites and/or hepatic hydrothorax 47 cause hypoxaemia and thus hyperventilation, hyperammonaemia and hepatic encephalopathy 48 induce hyperventilation per se.…”
Section: Alkalinising Factors In Patients With Liver Cirrhosismentioning
confidence: 99%
“…Significant correlations were found between dyspnea and fatigue. Previous study found significant correlations between chronic dyspnea and muscle fatigue (16,25) .…”
Section: Discussionmentioning
confidence: 89%
“…58 Seven (18%) studies did not report the country where the research was conducted. 49,65,66,73,74,76,77 Study settings include inpatient (16; 37%), [45][46][47][48][50][51][52][53][54][55][56][57]59,60,79,87 outpatient (11; 26%), 58,61,63,67,70,72,75,77,82,84,85 and both in-and outpatient clinical settings (1; 2%). 76 Fifteen (35%) studies did not specify the patient setting.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%